2014
DOI: 10.1002/pen.23854
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of short aramid fiber‐filled elastomer composites

Abstract: Short fiber reinforcement is a suitable way to improve the tribological properties of elastomers. However, rubbers products are often exposed to highly dynamic mechanical loadings. Hereby it is crucial to study the change in dynamic behavior due to the addition of short fibers. Therefore, these properties were investigated in terms of dynamic mechanical thermal analysis, heat build-up (HBU), and fatigue crack growth resistance under cyclic loadings for two different rubber compounds. A peroxide cured ethylene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…An increase in modulus was observed with increasing fiber content. Similar studies 9,35,36 have reported that an increase in fiber content increases the storage modulus of the polymer matrix. This effect was more pronounced for the addition of 5 phr jute fibers, and the addition of 2.5 phr practically did not increase the storage modulus.…”
Section: Dynamic Mechanical Thermal Analysis (Dmta)supporting
confidence: 49%
“…An increase in modulus was observed with increasing fiber content. Similar studies 9,35,36 have reported that an increase in fiber content increases the storage modulus of the polymer matrix. This effect was more pronounced for the addition of 5 phr jute fibers, and the addition of 2.5 phr practically did not increase the storage modulus.…”
Section: Dynamic Mechanical Thermal Analysis (Dmta)supporting
confidence: 49%
“…19 However, the degree of reinforcement generated by that solid particle is dependent on some important parameters, such as: aspect ratio, volume fraction, distribution, orientation, and interfacial interaction with rubber matrix. 20 Thus, data of morphometric parameters quantified from micro-CT (Table 3) are useful to support the rheological investigation described in the next section.…”
Section: Micro-dispersion Characterization Of Rockwool Fibers By Micro-ctmentioning
confidence: 93%
“…Fibers or particles embedded in a rubber matrix can effectively improve the comprehensive performances of materials, such as high strength, fatigue resistance, and corrosion resistance. This kind of composites has good applicability over recent years .…”
Section: Introductionmentioning
confidence: 99%